1985
DOI: 10.1172/jci112069
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma epithelial cells secrete thymic hormone but do not express class II antigens of the major histocompatibility complex.

Abstract: 17 thymomas were studied by indirect immunofluorescence for the presence of thymic hormones and antigens of the major histocompatibility complex (MHC). The thymoma epithelial cells (specifically identified by their keratin content) contained thymic hormones (thymulin and thymosin al), a finding corroborated by the observation of elevated thymulin serum levels. In contrast with normal or hyperplastic thymuses, thymoma epithelial cells did not express HLA-DR and HLA-DC antigens as assessed by immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Although MHC class I molecules were expressed on the thymoma neoplastic epithelial cells at a level comparable to that on normal thymic epithelial cells, expression of MHC class II molecules was generally decreased and varied from case to case, consistent with previous reports [19][20][21][22]. In addition, interestingly, there was a significant correlation between the expression of MHC class II molecules and the proportion of CD3 þ cells among the CD4 þ CD8 ¹ subset in a thymoma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although MHC class I molecules were expressed on the thymoma neoplastic epithelial cells at a level comparable to that on normal thymic epithelial cells, expression of MHC class II molecules was generally decreased and varied from case to case, consistent with previous reports [19][20][21][22]. In addition, interestingly, there was a significant correlation between the expression of MHC class II molecules and the proportion of CD3 þ cells among the CD4 þ CD8 ¹ subset in a thymoma.…”
Section: Discussionsupporting
confidence: 90%
“…The interaction between the T cell antigen receptor (TCR) on thymocytes and MHC antigen on thymic epithelium is believed to play an important role in selection of mature thymocytes [16][17][18]. Previous immunohistochemical analyses have demonstrated a reduced expression of MHC class II molecules on thymoma epithelial cells [19][20][21][22]. Thus, it seems reasonable to speculate that the abnormal T cell development in thymomas might be accompanied by the altered selection of newly generated T cells, and this in turn might lead to autoimmune disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…Marked increases in thymocyte MHCII expression in GBA KO mice might, thus, impact cell fate. MHCII may enable DP thymocyte depletion through pathological apoptosis, while stimulating positive selection during T-cell maturation (20,21). The latter may underlie the accumulation of mature CD4 + and CD8 + single-positive cells in GBA KO thymocytes in severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Okumura and co‐workers69 have suggested that the lack of functional medulla in the tumor might result in defective negative selection of T cells, favoring autosensitization against locally expressed autoantigens, such as AChR. Savino and colleagues72 showed that thymoma epithelial cells are defective in the expression of HLA class II molecules known to play an essential role in intrathymic T‐cell differentiation, which might explain thymoma‐associated defects in the thymic selection of T cells. Those investigators had previously shown that expression of a differentiation factor for human thymic epithelium—recognized by the anti‐p19 monoclonal antibody—is lost in thymomas, suggesting that, during malignant transformation, thymic epithelial cells acquire severe defects likely to give rise to defective T‐cell selection 73…”
Section: Evidence For Thymic Involvement In Mgmentioning
confidence: 99%